Sleep symptoms are essential features of long‐COVID – Comparing healthy controls with COVID‐19 cases of different severity in the international COVID sleep study (ICOSS‐II). (8th October 2022) - Merikanto, Ilona; Dauvilliers, Yves; Chung, Frances; Wing, Yun Kwok; De Gennaro, Luigi; Holzinger, Brigitte; Bjorvatn, Bjørn; Morin, Charles M.; Penzel, Thomas; Benedict, Christian; Koscec Bjelajac, Adrijana; Chan, Ngan Yin; et al.
Summary: Many people report suffering from post‐acute sequelae of COVID‐19 or "long‐COVID", but there are still open questions on what actually constitutes long‐COVID and how prevalent it is. The current definition of post‐acute sequelae of COVID‐19 is based on voting using the Delphi‐method by the WHO post‐COVID‐19 working group. It emphasizes long‐lasting fatigue, shortness of breath and cognitive dysfunction as the core symptoms of post‐acute sequelae of COVID‐19. In this international survey study consisting of 13, 628 subjects aged 18–99 years from 16 countries of Asia, Europe, North America and South America (May–Dec 2021), we show that post‐acute sequelae of COVID‐19 symptoms were more prevalent amongst the more severe COVID‐19 cases, i.e. those requiring hospitalisation for COVID‐19. We also found that long‐lasting sleep symptoms are at the core of post‐acute sequelae of COVID‐19 and associate with the COVID‐19 severity when COVID‐19 cases are compared with COVID‐negative cases. Specifically, fatigue (61.3%), insomnia symptoms (49.6%) and excessive daytime sleepiness (35.8%) were highly prevalent amongst respondents reporting long‐lasting symptoms after hospitalisation for COVID‐19. Understanding the importance of sleep‐related symptoms in post‐acute sequelae of COVID‐19 has a clinical relevance when diagnosing and treating long‐COVID.